Classification of the facets of lateral atlantoaxial joints in patients with congenital atlantoaxial dislocation - Ma, Fei; He, Hongchun; Liao, Yehui; Tang, Qiang; Tang, Chao; Yang, Sheng; Wang, Qing; Zhong, Dejun (European spine journal, 2020)
Purpose To investigate the morphological characteristics and para-positions of the facets of lateral atlantoaxial joints (FLAJs) in patients with congenital atlantoaxial dislocation (CAAD) and to propose a classification system for the FLAJs. Methods A total of 93 cases of CAAD were included in this retrospective study. The obliquity and slippage of the FLAJs in the sagittal and coronal planes were measured and observed in the CT images of all of the cases. The obliquity and slippage of the FLAJs represented the morphological characteristics and the para-positions, respectively, and were used as classification parameters. Accordingly, a classification system for the FLAJs was established. We additionally investigated the correlation between the classifications of the FLAJs and various types of CAAD. The classifications of the FLAJs in 34 patients with irreducible AAD (IAAD) were also investigated. Results One hundred eighty-six FLAJs in 93 patients were classified into 6 types (namely, A , B 1, B 2, C , D 1, and D 2) for obliquity and 3 types (namely, S 0 , S 1 , and S 2 ) for slippage. Among the 186 FLAJs, type B1 and type S 0 were the most common obliquity and slippage types, respectively. There were 11 combination types for obliquity and 5 combination types for slippage of bilateral FLAJ in 93 patients. Most of the patients (69.7%, 47/70) with anteroposterior AAD had accompanying slippage and anteversion of the FLAJ in the sagittal plane. Rotational AAD was found in 10 patients with asymmetrical slippage in both FLAJs in the sagittal plane. Lateral translational AAD was found in 6 patients with an S 1 -type FLAJ in the coronal plane. In 5 patients with lateral angular AAD, FLAJs of types D 1 and S 2 were observed on one side. Among the 34 patients with IAAD, 31 patients had both obliquity and slippage in the FLAJs on one or both sides. Conclusion The morphological characteristics and para-positions of the FLAJs on both sides largely determine the types of AAD in patients with CAAD. The types of obliquity and slippage of the FLAJ are related to the reducibility of AAD.